2017
DOI: 10.2169/internalmedicine.8341-16
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Uremic Syndrome-associated Encephalopathy Successfully Treated with Corticosteroids

Abstract: The encephalopathy that occurs in association with hemolytic uremic syndrome (HUS), which is caused by enterohemorrhagic Escherichia coli (E. coli), has a high mortality rate and patients sometimes present sequelae. We herein describe the case of a 20-year-old woman who developed encephalopathy during the convalescent stage of HUS caused by E. coli O26. Hyperintense lesions were detected in the pons, basal ganglia, and cortex on diffusion-weighted brain MRI. From the onset of HUS encephalopathy, we treated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Yada et al successfully treated a 14-year-old girl with STEC-HUS and acute encephalopathy with high-dose steroid pulse therapy Case Reports in Pediatrics (two courses of IV methylprednisolone 500 mg/day for 3 days) in association with plasma exchange, obtaining full recovery [14]. Hosaka et al described a 20-year-old woman who developed severe alteration of consciousness leading to coma and was treated with methylprednisolone pulse therapy (1000 mg/day for 3 days), with rapid clinical improvement and complete resolution of deep grey matter lesions on brain MRI [15]. On the contrary, Imataka et al reported on a 22-month-old boy unsuccessfully (cerebral death) treated with brain hypothermic therapy and steroid pulse therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Yada et al successfully treated a 14-year-old girl with STEC-HUS and acute encephalopathy with high-dose steroid pulse therapy Case Reports in Pediatrics (two courses of IV methylprednisolone 500 mg/day for 3 days) in association with plasma exchange, obtaining full recovery [14]. Hosaka et al described a 20-year-old woman who developed severe alteration of consciousness leading to coma and was treated with methylprednisolone pulse therapy (1000 mg/day for 3 days), with rapid clinical improvement and complete resolution of deep grey matter lesions on brain MRI [15]. On the contrary, Imataka et al reported on a 22-month-old boy unsuccessfully (cerebral death) treated with brain hypothermic therapy and steroid pulse therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies (cohorts after 2010), have better outcomes with lower mortality,13.9% (IQR:12.5 -22%)] [34]. Over the past two decades, high-dose intravenous mPSL pulse therapy (an approach already used to treat several neurological syndromes) has been used in various studies in the field of HUS to avoid the development of side effects and maintain long-term efficacy [22,[35][36][37][38]43]. In a previous study, a 14-year-old girl was successfully treated of STEC-HUS and acute encephalopathy with high-dose steroid pulse therapy (two courses of IV methylprednisolone 500 mg/day for 3 days) in association with plasma exchange, obtaining full recovery [37].…”
Section: Figurementioning
confidence: 99%
“…Furthermore, another study of 292 children with E. coli O157 infection [ 93 ] reported that fosfomycin should be administered in a rather smaller time window, during the first 2 days of illness, in order to reduce the risk of HUS. However, a case report in 2017 [ 94 ] described the evolution of a 20-year-old woman whose digestive symptoms improved after fosfomycin treatment four days from the beginning of gastroenteritis with EHEC O26, who was then diagnosed with HUS a day after treatment. This patient began supportive care treatment with improvements in symptoms but developed acute encephalopathy five days later.…”
Section: Pharmacologymentioning
confidence: 99%
“…Still, currently in use, methylprednisolone therapy has been extensively reported to exert neuroprotective effects and reverse CNS damage without sequelae [ 59 , 60 , 94 , 106 - 110 ].…”
Section: Pharmacologymentioning
confidence: 99%